Women, Gender and Terrorism - moslem karamzadi; fahimeh khansari fard (رهیافتهای سیاسی و بین المللی)
One of the most important aspects of contemporary terrorism is the gender terrorism against the mainstream of terrorism. The increasing the number of terrorist women, the growth of suicide attacks by women, the widespread use from modern technology in the recruitment of women by terrorist organizations and the expansion of women's employment at various levels of terrorist organizations lead to the global attention to this phenomenon. In analyze the female terrorism the most important questions are that; what are the motivations of women for membership in terrorist organizations and also the goals of terrorist organizations for employing women in terrorist actions? To answer this questions, this paper with review of history of women's involvement in terrorism, has been examined the women's motivations for membership, and the goals of terrorist organizations for women's employment. Women's goals are a set of personal, psychological, social, economic, and ideological motivations. On the other hand, terrorist organizations exploit women for the many strategical and tactical benefits. This article attempts to analyze this hypothesis by using the causal explanation method and content analysis, using the background of important terrorist organizations, especially al-Qaeda and the ISIL.